2020
DOI: 10.1101/2020.09.19.304618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanomechanical phenotypes in cMyBP-C mutants that cause hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a disease of the myocardium caused by mutations in sarcomeric proteins with mechanical roles, such as the molecular motor myosin. Around half of the HCM-causing genetic variants target contraction modulator cardiac myosin-binding protein C (cMyBP-C), although the underlying pathogenic mechanisms remain unclear since many of these mutations cause no alterations in protein structure and stability. As an alternative pathomechanism, here we have examined whether pathogenic muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 101 publications
1
6
0
Order By: Relevance
“…Much less is known about primary pathomechanisms triggered by MYBPC3 variants that do not cause protein haploinsufficiency, which is problematic because they are responsible for a substantial fraction of HCM cases 7,23,26 . To the best of our knowledge, the R502W strain is the first murine model for this type of variants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Much less is known about primary pathomechanisms triggered by MYBPC3 variants that do not cause protein haploinsufficiency, which is problematic because they are responsible for a substantial fraction of HCM cases 7,23,26 . To the best of our knowledge, the R502W strain is the first murine model for this type of variants.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domains of the protein are strongly bound to the thick filament through strong electrostatic interactions with different regions of myosin molecules 54,55 whereas the N-terminal domains are more dynamic and capable of regulating contraction by reversible interactions that stabilize the active state of thin filaments and the inactive state of thick filaments 56 . The central C3-C7 domains of cMyBP-C have traditionally been regarded as mere connectors of the N-and C-terminal regions of the protein (Figure 1B); however, this apparently minor functional role of C3-C7 domains does not agree with the fact that many missense HCM variants, including R502W, target these domains 23,26,57 . Indeed, recent reports have found that the central region of cMyBP-C interacts with myosin, as assessed both biochemically 24,40 and structurally 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations